2021
DOI: 10.1136/bmjopen-2020-039939
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dementia education and training on health and social care staff knowledge, attitudes and confidence: a cross-sectional study

Abstract: ObjectivesThe aim of this study was to establish the impact of dementia education and training on the knowledge, attitudes and confidence of health and social care staff. The study also aimed to identify the most effective features (content and pedagogical) of dementia education and training.DesignCross-sectional survey study. Data collection occurred in 2017.SettingsHealth and social care staff in the UK including acute care, mental health community care trusts, primary care and care homes.ParticipantsAll hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…A key part of using the intervention for shared decision‐making is the support activities for people affected by dementia and practitioners (see implementation box in Figure 3 ). This aligns with the literature on the importance of skill, education and training for practitioners 53 , 54 to enhance knowledge 55 , 56 and confidence in providing end of life care. 57 The logic model highlights areas of uncertainty in using the intervention, such as a priorities of care list (Figure 3 ).…”
Section: Discussionsupporting
confidence: 76%
“…A key part of using the intervention for shared decision‐making is the support activities for people affected by dementia and practitioners (see implementation box in Figure 3 ). This aligns with the literature on the importance of skill, education and training for practitioners 53 , 54 to enhance knowledge 55 , 56 and confidence in providing end of life care. 57 The logic model highlights areas of uncertainty in using the intervention, such as a priorities of care list (Figure 3 ).…”
Section: Discussionsupporting
confidence: 76%
“…Also, a note on the delivery method of the training course: COVID-19 pandemic circumstances required the course to be delivered online, but there is evidence that face-to-face methods increase the effectiveness of the training [ 18 ]; this is one point to improve in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable with the previous studies that found a significant correlation between the degree of dementia-specific cognizance and the overall quality of healthcare. [ 17 18 ] In the light of these findings, it can be suggested that dementia training programs should be held at the district level by the Health Ministry of India because educating the professionals as well as the general public is pivotal in tackling the increasing prevalence of the disease. The education could be provided in the form of pamphlets, informative videos on social media, and lectures at the undergraduate level.…”
Section: Discussionmentioning
confidence: 99%